Health Risk Assessment of Heavy Metals in Indoor Dust in Erbil City - Shami, Nadia M.; Yaba, Sardar P. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Indoor dust is a significant source of heavy metal exposure, posing potential health risks to residents. This study investigates the concentration and possible health risks of heavy metals in household dust in Erbil City, Kurdistan Region of Iraq, and assesses the associated health risks. 123 indoor dust samples were collected from various residential areas and analyzed using Energy Dispersive X-ray spectroscopy, an advanced technique that enables precise elemental detection. The metals assessed included aluminum (Al), iron (Fe), titanium (Ti), arsenic (As), chromium (Cr), nickel (Ni), cadmium (Cd), and lead (Pb). The highest mean concentrations were observed for aluminum (Al), particularly in the Northwest region (29209 mg/kg), while lead (Pb) exhibited the lowest concentration in the same Northwest region (28 mg/kg). Notably, elevated levels of titanium (Ti) were detected in the northern area, and cadmium (Cd) was most pronounced in the Northeast, reflecting spatial variation potentially linked to traffic emissions, construction activity, and indoor smoking. To evaluate the potential health implications, hazard quotients and hazard indices (HI) are calculated for both children and adults, focusing on non-carcinogenic risks through inhalation exposure in accordance with the United States Environmental Protection Agency guidelines. Although localized HQ values were higher for certain elements, such as Ti and Cd, all calculated HI values remained below the threshold value of 1. This indicates that under current environmental conditions, indoor dust in Erbil City is unlikely to pose significant non-carcinogenic health risks through inhalation.